1996
DOI: 10.1002/(sici)1097-4644(19960401)61:1<109::aid-jcb12>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Decreased heterogeneity of CS histone variants after hydrolysis of the ADP‐ribose moiety

Abstract: Sea urchin CS histone variants are electrophoretically heterogeneous when analyzed in two dimensional polyacrylamide gels (2D-PAGE). Previous results suggested that this heterogeneity is due to the poly (ADP-ribosylation) of these proteins. Consequently, native CS histone variants were subjected to different treatments to remove the ADP-ribose moiety. The incubation in 1 M hydroxylamine was not effective in eliminating the polymers of ADP-ribose from CS variants, and the treatment with sodium hydroxide was del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, two seminal studies published by Sajish www.nature.com/scientificreports www.nature.com/scientificreports/ et al have established a SIRT1 independent mechanism of action for RSV through other potential targets, such as mammalian phosphodiesterase-4 (PDE4) and poly-ADP-ribose polymerase-1 (PARP1) 21,22 . Interestingly, PDE4 degrades poly(ADP-ribose) polymer and recycles the ADP-ribose into adenosine monophosphate (AMP) units, resulting in a transient competitive inhibition of cAMP hydrolysis [23][24][25][26] . cAMPs regulate the localization, duration, and amplitude of cyclic nucleotide signaling.…”
mentioning
confidence: 99%
“…However, two seminal studies published by Sajish www.nature.com/scientificreports www.nature.com/scientificreports/ et al have established a SIRT1 independent mechanism of action for RSV through other potential targets, such as mammalian phosphodiesterase-4 (PDE4) and poly-ADP-ribose polymerase-1 (PARP1) 21,22 . Interestingly, PDE4 degrades poly(ADP-ribose) polymer and recycles the ADP-ribose into adenosine monophosphate (AMP) units, resulting in a transient competitive inhibition of cAMP hydrolysis [23][24][25][26] . cAMPs regulate the localization, duration, and amplitude of cyclic nucleotide signaling.…”
mentioning
confidence: 99%
“…In sea urchin sperm, the five histones are found in an unmodified form. By contrast , the CS histone variants are extensively poly(ADPribosylated) in unfertilized eggs [Imschenetzky et al, 1996b]. Shortly after fertilization, sperm histone variants SpH1 and SpH2B become phosphorylated.…”
Section: Post-translational Modifications Of Histones At Fertilizationmentioning
confidence: 99%
“…In contrast with sperm histones, the CS histone variants that organize the chromatin in sea urchin unfertilized eggs and zygotes and during the initial cleavage divisions are extensively poly(ADP-ribosylated). It was found that the poly(ADP-ribosylation) of CS histone variants changes in a cell cycle-dependent manner and is required for zygotic DNA replication [Imschenetzky et al, 1993;1996b]. This posttranslational modification is catalyzed by the poly(ADP-ribose) synthetase (PARP), a nuclear enzyme found in a wide variety of eukaryotic cells.…”
Section: Post-translational Modifications Of Histones At Fertilizationmentioning
confidence: 99%
“…This step is consistently blocked in vivo as well as in vitro by protein kinase inhibitors [Cothreen and Poccia, 1993;Cameron and Poccia, 1994]. Immunobiochemical evidence indicates that at an intermediate step of male pronucleus formation, sperm chromatin is organized into hybrid nucleoprotein particles formed by sperm-specific histones H1 (SpH1) and H2A-H2B (SpH2A-SpH2B), and by a subset of CS histone variants derived from maternal stores [Imschenetzky et al, 1991;1996a;1996b]. Therefore, in the context of the selective proteolysis of the complete set of sperm histones by the SpH-protease, these hybrid nucleoprotein particles containing a partial subset of sperm histones together with CS histone variants are a puzzling observation.…”
mentioning
confidence: 99%